Synthesis and EMW absorbing properties of nano SiC modified PDC–SiOC. Issue 25 (6th June 2016) - Duan, Wenyan; Yin, Xiaowei; Ye, Fang; Li, Quan; Han, Meikang; Liu, Xiaofei; Cai, Yanzhi
Abstract : Nano SiC modified silicon oxycarbide (n-SiC/SiOC) ceramics had special microstructure and phase composition that can lead to electric dipole polarization and interfacial scattering which eventually resulted in the strong absorption capability of n-SiC/SiOC. Abstract : Nano SiC modified silicon oxycarbide (n-SiC/SiOC) ceramics were prepared through the pyrolysis of a mixture of liquid polysiloxane and n-SiC with an average grain diameter of 30 nm. After adding n-SiC, palingenetic SiC nanograins with an average grain diameter smaller than 10 nm, and nanosized free carbon were gradually separated from the amorphous SiOC phase when the annealing temperature increased from 1100 °C to 1450 °C. The various interfaces among n-SiC, in situ formed SiC nanograins, nanosized carbon and amorphous SiOC phases can obtain interfacial scattering. Eventually, the electric dipole polarization and interfacial scattering enhanced the absorption properties. The minimal reflection coefficient (RCmin ) of the n-SiC/SiOC ceramics annealed at 1400 °C (n-SiC/SiOC-1400) reached −61 dB at 8.6 GHz. The widest effective absorption bandwidth (EAB) reached 3.5 GHz in the X-band, which indicates that the n-SiC/SiOC ceramics can be considered as high-performance microwave absorbing materials because of the strong absorption capability and wide absorption bandwidth.